Inverse kinematic and dynamic analysis of redundant measuring manipulator BKHN-MCX-04 - Khang, Nguyen Van; Dien, Nguyen Phong; Vinh, Nguyen Van; Nam, Tran Hoang (Vietnam Journal of Mechanics, 2010)
This paper deals with the problem of inverse kinematics and dynamics of a measuring manipulator with kinematic redundancy which was designed and manufactured at Hanoi University of Technology for measuring the geometric tolerance of surfaces of machining components. A comparison between the calculation result and the experimental measurement is also presented.